Characterization of a fast-growing mycobacteria, isolated from a healthy individual from Kelantan, Malaysia - Anis Fadhilah Zulkipli; Maria E. Sarmiento; Nyok-Sean Lau; Kai Ling Chin; Nur Hidayati MB; Zulaikah Mohamed; Fatin Syamimi Mohamad Zahidan; Nik Zuraina Nik Mohd Nor; Ezzeddin Kamil Mohamed Hashim; Pannerchelvam S; Siti Suraiya; Armando Acosta; et al. (Microbiology and Biotechnology Letters, 2024)
The human microbiome is critical to understanding health and disease. The presence of mycobacteria in the normal microbiome (mycobacteriome) holds significant interest for its potential role in autoimmunity, allergy, cancer, infections, and particularly in modulating immune responses to pathogenic mycobacteria and tuberculosis vaccines. In this regard, in the context of the study of the mycobacteriome in healthy individuals, the aim of this study was to characterize a Fast-Growing Mycobacteria (FGM) isolated from a healthy individual, which was characterized by: I) Genotypic studies: a) whole genome sequencing (WGS), b) phylogenetic study for 19 mycobacteria strains (general comparison) and 24 Mycolicibacterium fortuitum (Mfor) genomes (specific comparison), and c) homology study with Mfor strains and Mycobacterium tuberculosis (Mtb). II) Phenotypic studies: a) biochemical studies b) antimicrobial susceptibility testing (AST), c) temperature tolerance, d) tolerance to 5% NaCl, and e) photo-reactivity. III) Immunological study based on an antigenicity study using sera from pulmonary TB patients (PTB) and healthy individuals with positive tuberculin skin test (TSTp) or negative (TSTn). Based on the genotypic and phenotypic results, FGM-USM could be considered as a new strain, belonging to Mfor group, named Mycolicibacterium fortuitum strain kelantanesensis. The reactivity of PTB sera suggest the presence in the strain of homology to Mtb proteins expressed in vivo during infection. The homology and antigenicity results suggest the potential evaluation of the strain for the development of vaccine candidates against TB.